Evolving Nature of Cyber Conflict - Tan, Eugene E Guang (2018)
The understanding of the nature of cyber conflict is evolving and expanding, even as Singapore recognises the threat of deliberate online falsehoods. States need to develop holistic responses to keep up with these changes, and to protect the resilience of their systems and society.